Parvimico materdei gen. et sp. nov.: A new platyrrhine from the Early Miocene of the Amazon Basin, Peru1. Issue 134 (September 2019) - Kay, Richard F.; Gonzales, Lauren A.; Salenbien, Wout; Martinez, Jean-Noël; Cooke, Siobhán B.; Valdivia, Luis Angel; Rigsby, Catherine; Baker, Paul A.
Abstract: Three field seasons of exploration along the Río Alto Madre de Dios in Peruvian Amazonia have yielded a fauna of micromammals from a new locality AMD-45, at ∼12.8°S. So far we have identified the new primate described here as well as small caviomorph rodents, cenolestoid marsupials, interatheriid notoungulates, xenarthrans, fish, lizards and invertebrates. The site is in the Bala Formation as exposed where the river transects a syncline. U-Pb dates on detrital zircons constrain the locality's age at between 17.1 ± 0.7 Ma and 18.9 ± 0.7 Ma, making the fauna age-equivalent to that from the Pinturas Formation and the older parts of the Santa Cruz Formation of Patagonian Argentina (Santacrucian). The primate specimen is an unworn M 1 of exceptionally small size (equivalent in size to the extant callitrichine, Callithrix jacchus, among the smallest living platyrrhines and the smallest Eocene-Early Miocene platyrrhine yet recorded). Despite its small size it is unlike extant callitrichines in having a prominent cingulum hypocone. Based on the moderate development of the buccal crests, this animal likely had a diet similar to that of frugivorous callitrichines, and distinctly different from the more similarly-sized gummivores, Cebuella and C. jacchus . The phyletic position of the new taxon is uncertain, especially given the autapomorphic character of the tooth as a whole. Nevertheless, its unusual morphology hints at a wholly original and hitherto unknown Amazonian fauna, and reinforces the impression of the geographic separation of the Amazonian tropics from the more geographically isolated southerly parts of the continent in Early Miocene times.